Comparative analysis of rumen metagenome, metatranscriptome, fermentation and methane yield in cattle and buffaloes fed on the same diet - Malik, P.K.; Trivedi, Shraddha; Kolte, A.P.; Mohapatra, A.; Biswas, S.; Bhattar, A.V.K.; Bhatta, R.; Rahman, Habibar (Frontiers Media, 2023)
A study to compare the rumen microbial community composition, functional potential of the microbiota, methane (CH4) yield, and rumen fermentation was conducted in adult male cattle and buffaloes fed on the same diet. A total of 41 phyla, 169 orders, 374 families, and 1,376 microbial genera were identified in the study. Bacteroidetes and Firmicutes were the two most dominant bacterial phyla in both cattle and buffaloes. However, there was no difference in the abundance of Bacteroidetes and Firmicutes in the rumen metagenome of cattle and buffaloes. Based on the abundance, the Proteobacteria was the 3rd largest phylum in the metagenome, constituting 18–20% in both host species. Euryarchaeota was the most abundant phylum of the methanogens, whereas Methanobacteriales and Methanobrevibacter were the most abundant orders and genera in both species. The methanogen abundances were not different between the two host species. Like the metagenome, the difference between the compositional and functional abundances (metagenome vs. metatranscriptome) of the Bacteroidetes and Firmicutes was not significant, whereas the proteobacteria were functionally less active than their metagenomic composition. Contrary to the metagenome, the Euryarchaeota was the 3rd most functional phylum in the rumen and constituted ~15% of the metatranscriptome. Methanobacteriales were the most functional methanogens, accounting for more than 2/3rd of the total archaeal functionality. These results indicated that the methanogens from Euryarchaeota were functionally more active as compared to their compositional abundance. The CH4 yield (g/kg DMI), CH4 emission (g/kg DDM), dry matter (DM) intake, and rumen fermentation did not vary between the two host species. Overall, the study established a substantial difference between the compositional abundances and metabolic functionality of the rumen microbiota; however, feeding cattle and buffaloes on the same diet resulted in similar microbiota composition, metabolic functionality, and CH4 yield. Further studies are warranted to investigate the effect of different diets and environments on the composition and metabolic functionality of the rumen microbiota.